Assessment of environmental and farm business impacts of phosphorus policies in two European regions - Arata, Linda; Chakrabarti, Anwesha; Ekane, Nelson; Foged, Henning Lyngsø; Pahmeyer, Christoph; Rosemarin, Arno; Sckokai, Paolo (Frontiers in Sustainable Food Systems, 2022)
This paper presents analyses of the economic and environmental impact of relevant phosphorus management policy scenarios, using representative pig and poultry farms in the Emilia-Romagna region (Po River basin, Italy) and Niedersachsen region (Ems River basin, Germany) as case studies. The analysis was done by using a farm-level linear programming bioeconomic model developed for different farm and animal types – sows, fattening pigs, laying hens and broilers. The baseline for the assessed scenarios involved farms situated within the Nitrate Vulnerable Zones (NVZs) and therefore, were subject to indirect phosphorus fertilisation limitations via the Nitrates Directive (ND). The analysed phosphorus management policy scenarios included the implementation of two different balances of 8.7 kg and 4.35 kg of P per ha per year, inspired by the German Fertiliser Ordinance for phosphorus fertilisation implemented in 2007 and later updated from 2017 up to 2023, respectively. We also included a more rigorous zero P balance scenario. The results of the scenario simulations, based on model assumptions, reveal that the introduction of direct phosphorus management policies for pig and poultry farms situated in high livestock dense regions can be done without causing any significant impact on farm gross margin (around 2% of reduction) for both regions and all four animal types, except for sows and broiler production in the Ems River Basin (up to 12% of reduction). Selected technologies and methods, inspired by current practices, have been analysed for their cost efficiency to achieve the target P balance of the individual scenarios, including export of slurry out of the farm or export of separation solids. Results also highlight that the Nitrates Directive alone is not enough to handle the P issue in monogastric livestock farms.